Disinfection of 3D-printed surgical guides using virgin coconut oil (in vitro study) - Rania T. Khalil; Ahmed Alshimy; Eglal Elsherbini; Mervat E. Abd-Ellah (BMC, 2023)
Abstract Background/objective Disinfection of a 3D-printed surgical guide is of utmost importance as it comes into contact with hard and soft tissue during implant placement so it poses a potential risk of pathogenic transmission. Methods used for disinfection in the surgical field should be reliable, practical, and safe for the instruments and the patients. The objectives of this study were to compare the antimicrobial potential of 100% Virgin Coconut Oil, 2% Glutaraldehyde, and 70% Ethyl Alcohol used to decontaminate 3D-printed surgical guides. Materials and methods Thirty identical surgical guides were printed and cut into two halves (N = 60). Both halves were then contaminated with a defined amount of human saliva samples (2 ml). The first half (n = 30) was sub-grouped into three study groups which were immersed in one of the three disinfectants for 20 min as follows; group VCO was immersed in 100% Virgin Coconut Oil, group GA was immersed in 2% Glutaraldehyde, and group EA was immersed in 70% Ethyl Alcohol. The second half (n* = 30) was sub-grouped into three control groups which were immersed in sterile distilled water as follows group VCO*, group GA*, and group EA*. The microbial count was expressed as colony-forming units per plate and the comparison of the antimicrobial potential of the three tested disinfectants between the three study and three control groups was done using the One-Way ANOVA test. Results The culture results of three study groups revealed no bacterial growth with the highest % of reduction in the mean microbial count of the oral microorganisms (about100%) and an uncountable bacterial growth was shown between the three control groups (more than 100 CFU/plate) representing the baseline of the oral microorganisms. Therefore; statistically significant differences were found between the three control and three study groups (P < .001). Conclusion The antimicrobial potential of Virgin Coconut Oil was comparable and equivalent to Glutaraldehyde and Ethyl Alcohol with a significant inhibitory action against oral pathogens.